Lung Function and Respiratory Morbidity Among Informal Workers Exposed to Cement Dust: A Comparative Cross-Sectional Study - Kumar Dushyant; Gagandeep Kaur Walia; Niveditha Devasenapathy (Annals of Global Health, 2023)
Background: Cement dust is a significant source of occupational exposure affecting lung function and respiratory health. A higher burden of respiratory morbidity is known among factory workers involved in cement production. Globally or from India, there are no estimates of this burden from informal workers exposed to cement dust. Objective: To assess difference in lung function and respiratory symptoms among informal workers exposed to cement and those unexposed, using a comparative community based cross-sectional study from purposively selected areas in Delhi, India. Methods: Using a portable spirometer we measured lung function and collected respiratory symptoms from conveniently sampled informal workers (n = 100) exposed to cement dust, 50 indoor informal workers (tailors), and 50 outdoor (vegetable) vendors. Regression analyses were performed to compare respiratory symptom score and lung function parameters, adjusted for age, body mass index, smoking, socioeconomic status, and years of occupational exposure. Findings: Exposed workers had significantly lower lung function (PEF = –750 ml/s and –810 ml/s and FEV1/FVC (%) = –3.87 and –2.11) compared to indoor and outdoor groups, with three times higher chronic respiratory symptoms when compared to the unexposed groups. The cement dust exposure was observed to be associated with PEF (mean difference (MD) = –0.75L, 95%CI = –1.36 to –0.15, p = 0.01), %FEV1/FVC (MD = –3.87, 95%CI = –6.77 to –0.96, p = 0.03) and respiratory symptoms (p < 0.001). Conclusion: This study generates evidence regarding the respiratory burden of occupational exposure among vulnerable informal workers. There is an urgent need for policy reforms to safeguard health from occupational exposures, especially among informal workers.